Prolactin, Luteinizing Hormone and Steroid Hormone Concentration in Punjab Brown (PB3) Birds Immunized Against Vasoactive Intestinal Peptide During the Early Stages of Egg Production - Reddy, I.J.; Kiran, G. Ravi; Mondal, S.K.; Anandan, S. (International Journal of Poultry Science, 2007)
This study aims at the effects of active immunization against chicken Vasoactive Intestinal Peptide (chVIP) on plasma prolactin (PRL) concentration, concentration of Luteinizing Hormone (LH) profile its interval and duration, progesterone (P4), estradiol (E2β), intersequence pause days and egg production in birds during the initial stages of egg production from 20-36 weeks of egg lay in PB3 birds. Twenty-four PB3 birds of same age group were divided into two groups of twelve in each. Birds in control group were administered s/c with placebo. Equal volume of chVIP immunogenic protein was administered to treated group from 17th week of age to 36 weeks of age at an interval of four weeks. Hormonal profiles of immunized and control birds were quantified at weekly intervals from 17th to 36th weeks of age in both the groups for prolactin, LH, estradiol, progesterone. Egg production and pause days were recorded in both the groups. At 31st weeks of age, blood samples from chVIP immunized and control birds were obtained every 4 h for 48 hours to study the surges of LH. In immunized PB3 birds (against ch VIP) plasma PRL concentration was lower (p<0.01) with high concentrations of E2β, P4, LH and, its 4h LH surges, in plasma (p<0.01). Significantly higher egg production (9.71%), less pause days were observed in chVIP immunized birds. It is mainly attributed due to low PRL concentration, associated with high concentrations of LH (with regular interval and duration of LH surges), E2β and P4 concentration required for egg formation and subsequent ovulation. In conclusion, chVIP immunization advanced the LH surges, for release of matured oocyte, egg formation and egg lay enabled the birds to lay eggs at regular intervals due to active immunization against chVIP. Results indicate that control of chVIP may lead to more egg production with shorter duration of LH surges.